2021
DOI: 10.3389/fnins.2021.611451
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging Detects Acute Pathology-Specific Changes in the P301L Tauopathy Mouse Model Following Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) has been linked with tauopathy. However, imaging methods that can non-invasively detect tau-protein abnormalities following TBI need further investigation. This study aimed to investigate the potential of diffusion tensor imaging (DTI) to detect tauopathy following TBI in P301L mutant-tau-transgenic-pR5-mice. A total of 24 9-month-old pR5 mice were randomly assigned to sham and TBI groups. Controlled cortical injuries/craniotomies were performed for TBI/sham groups followed by DTI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 79 publications
1
5
0
Order By: Relevance
“…In these conditions, the interpretation of higher fractional anisotropy values as solely indicative of increased white matter integrity may not hold true. Some studies indicated that astrocytes undergoing structural remodeling postinjury, thereby driving glial scarring, lead to anisotropic tissue microstructure causing an increase in fractional anisotropy . Notably, a 2011 study performing a histological analysis showed that glial fibrillary acidic protein (GFAP), which is a marker for gliosis, was significantly positively correlated with fractional anisotropy and axial diffusivity.…”
Section: Discussionsupporting
confidence: 90%
“…In these conditions, the interpretation of higher fractional anisotropy values as solely indicative of increased white matter integrity may not hold true. Some studies indicated that astrocytes undergoing structural remodeling postinjury, thereby driving glial scarring, lead to anisotropic tissue microstructure causing an increase in fractional anisotropy . Notably, a 2011 study performing a histological analysis showed that glial fibrillary acidic protein (GFAP), which is a marker for gliosis, was significantly positively correlated with fractional anisotropy and axial diffusivity.…”
Section: Discussionsupporting
confidence: 90%
“…Deletion of Rubicon in the macrophages abolished the degradation of all tested proteins and the increase in eIF2α S51 phosphorylation (Supplementary Figure 1). We next determined in HCN2 neuronal cells and in BV2 microglia the abilities of AR12 and neratinib to reduce the expression of mutant forms of APP and Tau [26][27][28][29]. AR12 and the drug combination reduced the expression of Tau 301L which trended to be less than the reduction of wild type Tau (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…From the perspective of neuroinflammatory-related changes in brain white matter, which are often reflected through DTI (Ji et al, 2017;Soni et al, 2021;Ouellette, 2022), all the three DTI studies included in this review suggested the abnormal changes in white matter in COVID-19 patients with memory symptoms (Lu et al, 2020;Silva et al, 2021;Huang C. et al, 2022;Huang S. et al, 2022), indicating the involvement of neuroinflammatory factors in these symptoms. Fernández-Castañeda et al found that even mild COVID-19 infections could result in significant brain inflammation followed by brain cell dysregulation (e.g., loss of oligodendrocytes in white matter), and this would be expected to predict cognitive problems (Fernández-Castañeda et al, 2022a).…”
Section: Discussionmentioning
confidence: 91%